AKTIVITAS PEREMPUAN PENJAJA MAKANAN ASONGAN DI SEKITAR TERMINAL SICINCIN - Roza, Elsa Melia; Yulkardi, Yulkardi; Fitlayeni, Rinel (Pendidikan Sosiologi, 2013)
Women are very important in the development potential. It is proved by the emergence of womens emancipation in all sectors, one of them is in the informal sector. The involvement of women in the informal sector has limited to resources and access. As a result, in the business options that can be entered also has range in some specific areas such as food hawkers peddling. The background of this issue is women itinerant food vendors in performing activities where she has to leave the family in a period of 9-10 hours a day. Before she goes home or goes to work, she has to do homework at the same time. The objectives of this study were 1). To describe the activity of female itinerant food vendors around Terminal Sicincin, and 2). To analyze the constraints faced by women in the work of itinerant food vendors.The theory used is the theory of Exchange (Exchange-Behavior) by George Homans. This study used qualitative methods with descriptive type. Data was collected through observation, interviews, and documentary studies. Decision madeby the informant porpousive sampling or based on certain criteria. Data analys is used the model data analysis Milles and Huberman.Based on the results obtained the following conclusions: first, Itinerant food vendors female activity, which can beseen from: 1). Description of the allocation of time, ie work outside the home as an itinerant food vendors conducted from 08.00 am until 17.00 pm. 2). Interaction among fellow itinerant food vendors see the cooperation, competition, and conflict. 3). Tips market mastery of the situation, which used the day off, buyers want to attend, give discounts to buyers, the established image salted egg and boiled bananas males. Second, the constraints experienced by women hawkers food vendors are obstacles in the work, the driver and passenger buses are not friendly, the absence of the pump, and the buyer on certain days.